Reconstruction of Two Wall Orbital Fractures: Experience With the 3D Titan Implant and Intraoperative Computed Tomography. Issue 4 (December 2022) - Holan, Cole A.; Yan, Derek J.; Hancock, Ellen; Harshbarger, Raymond
Background: Orbital fractures are common in maxillofacial trauma and have varying anatomical deficits depending on the mechanism of injury. Orbital floor fractures are most common, but many patients suffer from two wall-floor and medial wall defects. Precise reconstruction and positioning of the orbital implant post traumatic injury can be technically challenging, especially in two wall fractures. We present our experience using the 3D Titan implant on a series of 7 patients with combined medial wall and orbital floor fractures. Methods: A retrospective chart review was performed of patients with combined medial wall and orbital floor fractures treated with 3D Titan between February 2016 and June 2020. The inclusion criteria were unilateral combined medial and orbital floor fractures due to traumatic etiologies, no previous history of orbital trauma, age older than 18 years, a contralateral healthy orbit, and a clinical follow-up of at least 1 month. Variables and outcomes included patient age, gender, mechanism of injury, visual defects, post-op infections, enophthalmos, proptosis, and diplopia. An O-arm intraoperative CT scanner was used to verify the implant position. Results: Ten patients presented with combined medial wall and orbital floor fractures, 3 were lost to follow-up. There were 6 men and 1 woman, and their ages ranged from 24 to 57 (mean age 38). Follow-up time ranged from 4 to 52 weeks, and a mean of 20 weeks. None of the patients experienced intraoperative complications such as hemorrhage, soft tissue incarceration, or acute optic neuropathy. No patients had postoperative infection or any change in visual acuity. All patients had satisfactory implant positioning as verified by intraoperative CT. Conclusions: The prefabricated design of the 3D Titan along with use of intraoperative CT guidance allows for efficient and precise reconstruction of combined medial wall and orbital floor fractures.